2007
DOI: 10.1111/j.1439-0469.2006.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal similarities and differences among four Neotropical Elateridae (Conoderini and Pyrophorini) and other related species, with comments on the NOR patterns in Coleoptera

Abstract: This work deals with the comparative cytogenetic analysis of four Neotropical Elateridae species and reviews the nucleolar organizer region (NOR) patterns on Coleoptera chromosomes, for the first time. The cytogenetic characterization of Conoderus malleatus (Conoderini), Pyrearinus candelarius, Pyrophorus divergens and Pyrophorus punctatissimus (Pyrophorini) was accomplished through the study of mitotic and meiotic cells submitted to standard (Giemsa) and differential staining [silver impregnation and GC-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…The most common distribution pattern described for this insect order is the presence of one autosomal pair involved in nucleolar organization (reviewed in the study by Schneider et al, 2007). These results were largely observed using silver nitrate staining, which detects only active nucleolar organizer regions.…”
Section: Mapping Of Repetitive Dnas In D Geminatus Dc Cabral-de-mellmentioning
confidence: 59%
“…The most common distribution pattern described for this insect order is the presence of one autosomal pair involved in nucleolar organization (reviewed in the study by Schneider et al, 2007). These results were largely observed using silver nitrate staining, which detects only active nucleolar organizer regions.…”
Section: Mapping Of Repetitive Dnas In D Geminatus Dc Cabral-de-mellmentioning
confidence: 59%
“…In E. caribaeus, the nucleolar organizer region is located in the sex bivalent, differing from the most common pattern detected in Coleoptera, that is the location of NORs in one autosomal pair (Moura et al 2003;Almeida et al 2006;Schneider et al 2007b). The observation of rDNA sites on the X and Y chromosomes of E. caribaeus using the FISH technique suggests the occurrence of fusion between an autosomal pair, carrying rDNA sequences, and the sex chromosomes, with the fusion also being responsible for the diploid number reduction in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique. Therefore, despite that the NORs data did not correspond to 1% of all Arachnida species taxonomically described, NORs located on the terminal region of one or two chromosome pairs seem to be widespread in representatives of this group.…”
Section: Discussionmentioning
confidence: 99%